Burst-aware data fusion for microblog search. Issue 2 (March 2015) - Liang, Shangsong; de Rijke, Maarten
Highlights We tackle the problem of microblog search differently, by data fusion. We propose to integrate temporal characteristics into data fusion. We propose a novel and effective probabilistic data fusion model for microblog search.